Outcome of management of complicated extragonadal teratoma in a resource poor setting - L O Abdur-Rahman; Suleiman Baba; K T Bamigbola; I Olaoye; A O Oyinloye; A A Nasir; J O Adeniran (Wolters Kluwer Medknow Publications, 2013)
Background: Extragonadal teratomas (EXGTs) are ubiquitous in the human body; hence, they have varied presentation. In underdeveloped areas presentation and management are affected by socio-economic, cultural and health facilities factors. The aim of this study was to review the outcome of management of complicated EXGT in a tertiary health centre. Materials and Methods: A review data of paediatric patients with EXGT was done between January 1999 and December 2012. Variables reviewed were bio-data, mode of presentation and site of tumour, comorbidity, treatments and outcome. The data was analysed with Statistical Package for Social Sciences (SPSS (R)) version 16.0. Results: There were 21 complicated EXGT (77.8%) among 27 children, age ranges from 4 days to 16 years (median = 2 years). Male:Female ratio of 1:2. The complications per region of the body at presentation were cervical 4 (66.7%), mediastinal 2 (100%), abdominal 3 (75%) and sacrococcygeal 12 (75%). The complications were respiratory distress 6, intestinal obstruction 5, faecal incontinence 2, bladder outlet obstruction 3, malignant transformation 5, ruptured sacrococcygeal teratoma 2, ulcerated tumour 2, anaemia 3 and malnutrition 3. There were 5 (23.8%) progressive disease post-excision outside our facility. Excision biopsy was successful in 19 (85%) patients two of which had neoadjuvant cytotoxic therapy. Overall mortality was 5 (23.8%) (septicaemia, anaemia, respiratory distress, renal failure) and post-excision mortality was 11.8% (endotracheal tube blockage and progressive disease). Conclusion: Delay presentation (due to local belief, ignorance and poverty) malnutrition, sepsis, malignant transformation characterised presentation of children in this study and the lack of paediatric intensive care unit facility and intensivists compromised survival of children with EXGT.